"Along for the Ride": A Qualitative Study Exploring Patient and Caregiver Perceptions of Decision Making in Cancer Care. Issue 1 (June 2020) - Holdsworth, Laura M.; Zionts, Dani; Asch, Steven M.; Winget, Marcy
Background. Shared decision making is a cornerstone of an informed consent process for cancer treatment, yet there are often many physician and patient-related barriers to participation in the process. Decisions in cancer care are often perceived as relating to a discrete, treatment decision event, yet there is evidence that decisions are longitudinal in nature and reflect a multifactorial experience.Objective. To explore patient and caregiver perceptions of the choices and decision-making opportunities within cancer care.Design. Qualitative in-depth interviews with 37 cancer patients and 7 caregivers carried out as part of an evaluation of a cancer center's effort to improve patient experience.Results. Participants described decision making related to four distinct phases in complex cancer care, with physicians leading, and often limiting, decisions related to disease assessment and treatment options and access, and patients leading decisions related to physician selection. Though physicians led many decisions, patients had a moderating influence on treatment, such that if patients did not like options presented, they would reconsider their options and sometimes switch physicians. Patients had various strategies for dealing with uncertainty when faced with decisions, such as seeking additional information to make an informed choice or making a conscious choice to defer decision making to the physician.Limitations. Patients were sampled from one academic cancer center that serves a predominantly Caucasian, Asian, and Hispanic/Latino population and received complex treatment.Conclusion. Because of the complexity of cancer treatment, many patients felt as though they were a "passenger" in decision making about care and did not lead many of the decisions, though many patients trusted their doctors to make the best decisions and were comforted by their expertise.